Thrombotic risk assessment in 185 WHO-defined essential thrombocythemia patients: single center experience - Dambrauskiene, Ruta; Gerbutavicius, Rolandas; Juozaityte, Elona; Gerbutaviciene, Rima (Contemporary Oncology/Współczesna Onkologia, 2015)
Thrombosis risk in essential thrombocythemia (ET) patients can be assessed using different prognostic systems. Conventional risk factors include age more than 60 years and history of previous thrombosis. In addition, other factors such as JAK2 V617F mutations, cardiovascular risk factors, leukocytosis more than 11 × 109/l, thrombophilic factors and platelet count more than 1500 × 109/l are used in different hematology centers as high-risk features for thrombosis. Our study compared different risk model groups for thrombosis in 185 WHO-defined ET patients at the Hospital of Lithuanian University of Health Sciences Kaunas Klinikos. We found that patient distribution in low, intermediate- and high-risk groups varies using different risk stratification models. The biggest difference in risk assignment is evident in patients who are older than 60 years and have no other risk factors and in patients who are younger than 60 years but have other risk factors. This observation suggests that new prospective randomized clinical trials are needed to better stratify patients at risk for thrombosis.